ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT KRIMINALITAS DI INDONESIA DARI PENDEKATAN EKONOMI - Florentius Nugro Hardianto (Bina Ekonomi, 2009)
Economic model assumes that an individual committing crimes is rational because the income which is generated through illegal occupations has greater expected utility than the legal. The expected utility which is the result of cost-benefit analysis will be weighted whether if illegal or legal occupations committed or not. Therefore, some experts developed supply of offense function as economic model, which indicates the factors affecting the total number of crimes as empirical study. The application  of supply of offense function supported with multiple  linear regression function, the factors affecting the total number of crimes  in Indonesia have following  results: wage  rate variables  indicated a negative and significant result and government expenditure  variables indicated positive and significant  result,  but the imprisonment  rate variables did not have significant result with  the total number of crimes in Indonesia.